The effect of tannic acid on the digestibility of pig feeds - Van Niekerk, B. D. H.(Barend Daniel Human) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.Agric.) -- University of Stellenbosch, 1957.